URBAN ECOSYSTEM SERVICES: TREE DIVERSITY AND STABILITY OF PM10 REMOVAL IN THE METROPOLITAN AREA OF ROME - Manes, F.; Silli, V.; Salvatori, E.; Incerti, G.; Galante, G.; Fusaro, L.; Perrino, C. (Annali di Botanica, 2014)
Urban vegetation, and particularly urban forests, are known to provide important ecosystem services, such as urban air quality improvement by removing gaseous and particulate pollutants. The amount of PM10 removed by urban and periurban trees of the metropolitan area of Rome (evergreen broadleaves, deciduous broadleaves and conifers) was estimated by considering the minimum and maximum PM10 concentration values recorded in the Municipality of Rome during the years 2003 and 2004. The results of these simulations have been used to map the Ecosystem Service of PM10 removal by the three functional groups in the five Sanitary Districts of the Municipality. Given the spatial uniformity of PM10 levels in the urban area, the highest amount of PM10 deposition rates, during the whole period, are those of the Sanitary District with the largest vegetation cover (RMD). It is also interesting to highlight that the highest deposition fluxes, for the three functional groups, were estimated for the 2004 summer period, in concurrence with the highest mean values of Leaf Area Index. Our results confirm the crucial role of vegetation in supporting significant Ecosystem Services as air quality improvement, highlighting the importance of biodiversity and green infrastructures in sustain and enhance benefits provided by trees.